Remaking Central Europe : the League of Nations and the former Habsburg lands - Becker, Peter, 1962-; Wheatley, Natasha (Oxford : Oxford University Press, 2021)
Over the last two decades, the 'new international order' of 1919 has grown into an expansive new area of research across multiple disciplines. With the League of Nations at its heart, the interwar settlement's innovations in international organizations, international law, and many other areas shaped the world we know today. This book presents a study of the relationship between this new international order and the new regional order in Central and Eastern Europe after the collapse of the Habsburg empire.
This edition previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 11, 2021).
Keywords: Europe, Central -- History -- 20th century; League of Nations; History; European history